Determinants of prevalence, awareness, treatment and control of high LDL-C in Turkey - (:unkn) unknown (My University, 2016)
0

Objective: High blood cholesterol is one of the main modifiable risk factors for cardiovascular diseases (CVDs). The aim of the study is to determine the factors associated with the prevalence, awareness, treatment, and control of high "low-density lipoprotein-cholesterol" (LDL-C) among adults aged >=20 years in Turkey.Methods: We used data from Chronic Diseases and Risk Factors Survey conducted in 2011-2012. The presence of high LDL-C, lipid-lowering treatment eligibility, and achievement of target LDL-C were defined according to the third Adult Treatment Panel guidelines on treatment of high cholesterol. Multivariate logistic regression analyses were performed to determine the associations between participant characteristics and high LDL-C prevalence, awareness, treatment, and control.Results: Framingham risk score categorization was performed for 13121 individuals aged >=20 years. Approximately, 28% of the participants presented with high LDL-C. Among those with high LDL-C, 55.8% were aware of their situation; among those aware of high LDL-C, 46.9% were receiving lipidlowering medication, and 50.6% of individuals who were receiving treatment achieved target LDL-C levels on the basis of their coronary heart disease (CHD) risk. Control of high LDL-C was negatively associated with the presence of diabetes mellitus (odds ratio: 0.36, 95% CI: 0.27-0.49, p<0.001).Conclusion: Despite the high awareness rates, there was a high proportion of adults who did not receive treatment or achieve recommended levels of LDL-C during treatment. The low treatment and control levels among individuals based on their CHD risk levels call for a better application of recommendations regarding personal preventive measures and treatments in Turkey.
Keywords: Kalp ve Kalp Damar Sistemi